Potential New Approaches for Diagnosis of Alzheimer's Disease and Related Dementias - Turner, R. Scott; Stubbs, Terry; Davies, Don A.; Albensi, Benedict C. (Frontiers in Neurology, 2020)
Dementia is an umbrella term - caused by a large number of specific diagnoses, including several neurodegenerative disorders. Alzheimer's disease (AD) is now the most common cause of dementia in advanced countries, while dementia due to neurosyphilis was the leading cause a century ago. Many challenges remain for diagnosing dementia definitively. Some of these include variability of early symptoms and overlap with similar disorders, as well as the possibility of combined, or mixed, etiologies in some cases. Newer technologies, including the incorporation of PET neuroimaging and other biomarkers (genomics and proteomics), are being incorporated into revised diagnostic criteria. However, the application of novel diagnostic methods at clinical sites is plagued by many caveats including availability and access. This review surveys new diagnostic methods as well as remaining challenges - for clinical care and clinical research.